Validation of Patient Intrinsic Factors on Pre-Delay Coronary CT Scan Angiography (Coronary CTA) Bolus Tracking (International Journal of Scientific Research in Science and Technology, 2024)
Background: There is a variation in the pre-delay scan time on the Caronaria CTA tracking bolus examination, which give a constitution against the acquisition time and the contrast. Purpose: This study aims to determine the influence’s intrinsic factors on the pre-delay scan time. Method: Analytical research with a retrospective approach’s cross-sectional design measures independent variables: aortic diameter, systolic blood pressure, age, heart rate (HR), urea, creatinine, and body mass index (BMI). The dependent variables: the time pre-delay scan is performed simultaneously; its properties are momentary and observed under current conditions. Each object was observed three times, then the data normality and influence relationships between variables were analyzed with the bivariate and multivariate analysis approaches. Data was surveyed in June–August 2023 at a Hospital in Jakarta. Results: Bivariate analysis showed a significant relationship between aortic diameter and pre-delay scan time with a value r = 0,577, having a positive pattern, as well as having a dependency 33.3% with p = 0,000 significance. While a very strong relationship is indicated by systolic blood pressure with r = 0.534 value and positive patterns, has a dependence of 30.4% with p = 0.000 significance value. Other instrumental factors: creatinine and BMI have a moderate relationship with r = 0.308 and r = 0.338 and are positive with a determination coefficient of 0.095 and 0.115. Urea, age, and heart rate have r = 0.174, 0.200, and 0.116. The determination coefficient values are under 0.04. Conclusion: The intrinsic factors: aortic diameter, systolic pressure, creatinine, urea, age, and heart rate have influenced positive CTA scan delays although different determination coefficients. Keywords: CTA Coronarya, bolus tracking, pre-delay scan time, aortic diameter, systolic blood pressure.